Evaluation of thermomechanical properties of epoxy–basalt fibre composites modified with zeolite and silsesquioxane. Issue 5 (13th June 2017) - Matykiewicz, Danuta; Lewandowski, Krzysztof; Dudziec, Beata
Abstract: The aim of this study was to verify the influence of zeolite and silsesquioxane (POSS) addition on thermo-mechanical properties of basalt fiber reinforced epoxy composites. The dynamic mechanical thermal analysis was conducted with different frequencies at bending mode. The mechanical properties were determined at static tensile test and Charpy impact strength method. The structure of composites was determined by scanning electron microscopy. The thermal stability was characterized by thermogravimetric analyses in inert and oxidizing atmospheres. The impact strength and thermal stability of the composites with zeolite and silseqioxane were higher than the reference sample. Thus, these composites can be used as thermally stable materials with high stiffness.